Anomali Geomagnet; Kaitannya dengan Zone Mineralisasi di Daerah Malingping, Bayah dan Sekitarnya, Kabupaten Lebak, Propinsi Banten - W.H Simamora (Jurnal Geologi dan Sumberdaya Mineral, 2006)
Magnetic anomaly in the Malingping - Bayah and surrounding areas, ranging from -650 nT to +270 nT, can be divided into three groups. The first group is the low anomaly with a value range from -650 nT to -250 nT, the second group is middle anomaly with a value range from -250 nT to + 50 nT, and the third group is high anomaly with a value range from + 50 nT to +270 nT. Low anomaly zone is thought to be the effect of intrution of acid rocks which is located in 500 to 2000 m depth. This is supported by the existing of granodiorite intrusion of Cihara (Tomg) that also coincides with low anomaly zone. The granodiorite intrusion is thougt to have played an important role in sulfide, gold (Au), and silver (Ag) mineralization which is found in the Cikotok and Cirotan areas.Â Keywords : Geomagnetic anomalies, Malingping, granodiorite of CiharaÂ